1-FB-1 DC-DC Converter Power Loss Analysis Cost - Gólcher Barguil, Luis Alejandro (2019)
A power loss analysis of the new 1-FB-1 DC/DC converter is proposed. The resulting model can be used to better predict the real DC-DC conversion rates that will be obtained when practical elements are implemented; as well as, a better heat loss estimation. Four distinct power loses are incorporated to the ideal canonical model: copper power loss at the transformer, transistor conduction power loss, diode conduction power loss and equivalent series resistor power loss at the output capacitor. The loss analysis establishes the framework to determine its feasibility for being used as a power supply in portable computers, hand-held devices, and communication equipment.